Unmet Need for Contraception and its Associated Factors among Married Women of Reproductive Age in Simichaur VDC of Gulmi District - Kandel, NR (Health Prospect, 2018)
Background Nepal Demographic Heath Survey conducted in 2006, has indicated 26.4 percent of unmet need among married women of reproductive age had unmet need at national level. Unmet need for limiting was highest (15.2%) where as spacing method constitutes at 9.4 percent. At western region, the vary region where the Gulmi district is situated unmet need is 32.4 % with 36.6 % of married women of reproductive age currently using contraceptives is lower than at the national level (44.2%).The objective of the study was to find out the various factors associated with the unmet need for contraception among married women of reproductive age group in Simichaur VDC of Gulmi district Methods It was a descriptive, cross sectional, community based study. Altogether 131 married women of reproductive age were interviewed while the systematic random sampling method was designed for sampling procedure. Interview was done using semi-structured questionnaire for data collection. Results Among 131 Married women of reproductive age, 42 percent were found currently using modern contraceptive method. Forty eight percent of the married women of reproductive age had unmet need for contraception, 29.7 percent for limiting and 18.3 percent for spacing. Less than a half of the respondent (45.8 percent) were able to name all seven modern contraceptive methods with the correct information about their source Conclusion The unmet need for family planning was high and the major reason for non-use of contraception were absence of husband, fear of side effect and having no information about contraceptives. So, Program that focuses on correct information sharing about contraceptives with couple should be designed, communication and discussion about family planning between spouses, programs that encourage the involvement of men in family planning should be developed and implemented. DOI: http://dx.doi.org/10.3126/hprospect.v11i0.7423 Health Prospect 2012;11:11-14